REVIEW PAPER ON AUTOMATED HYDROPONICS - Ms. Konade S. B; Mr. Khilari V. S; Miss. Aswale L. S; Miss. Jadhav A. F. (International Engineering Journal For Research & Development, 2022)
The explosion in human population has left researchers scrambling for solutions on how to feed the world. Furthermore, rural-urban immigration has on the one hand left the farms in the rural areas devoid of farmers and on the other hand has left the urban areas over-populated. Hydroponics is a form of agriculture where crops are grown without soil. This technique allows the farms to follow the farmers to the urban area. In addition, the fact that no soil is needed, allows hydroponic system to be stacked vertically (also known as vertical farming) to save space. The final frontier in hydroponics is automation. It will allow one farmer to work more than one job and cultivate more than one farm simultaneously. Growing certain plants and vegetables in remote areas such as deserts and the north and South Pole can be a challenge because of the extreme outside weather. very few species of plants thrive in such situations and are often not used as a food source. In this study, we created a system that can grow common plants and vegetables and can operate without depending on outside climate. we achieved this by using a technique called automated hydroponics. Hydroponics is a method of growing plants without using soil. The system was automated using microcontrollers and sensors to keep human intervention at a minimum. An internet of Things (IOT) network was created to improve reliability and allow remote monitoring and control if needed. The user is only required to plant a seeding and set initial parameters.